SISTEM INFORMASI TOP UP GAME (STUDI KASUS LOGAM GAMES STORE) - Manurung, Immanuel H G; Donets, Felix; Sibero, Alexander F.K. Sibero; Khair, Husnul (JTIK (Jurnal Teknik Informatika Kaputama), 2026)
This study aims to design and develop a web-based information system for game top-up services at Logam Games Store, providing users with a fast and efficient way to purchase digital items. The system was developed using the Waterfall method through the stages of requirement analysis, system design, implementation, and testing. Technologies used include PHP, MySQL, HTML, and payment integration via Midtrans Snap API (Sandbox). The system’s main features include user registration and login, game selection, input of game account data, top-up amount selection, payment processing, and transaction history display. The top-up mechanism is semi-automated, with the admin manually delivering the purchased items via a third-party platform, namely Itemku. The system was tested using Black Box Testing, and results showed that all functions performed as expected based on user needs. This system is expected to offer a practical solution for small-scale game top-up services and has the potential for further development toward full automation.